New insights into Southern Caucasian glacial–interglacial climate conditions inferred from Quaternary gastropod fauna. (3rd May 2020) - Richter, Christiane; Wolf, Daniel; Walther, Frank; Meng, Stefan; Sahakyan, Lilit; Hovakimyan, Hayk; Wolpert, Tilmann; Fuchs, Markus; Faust, Dominik
ABSTRACT: In the present study, we performed gastropod analyses on loess–palaeosol sequences from northeast Armenia (Southern Caucasia) covering at least three glacial–interglacial cycles. The elaborated ecostratigraphy shows significant patterns of species composition related to the succession of pedocomplexes and loess, respectively. Pedocomplexes included species that can be associated with high‐grass to forest‐steppe biomes, indicating increased humidity for these sections compared to the loess layers. In contrast, loess layers that relate to glacial periods are associated with gastropod species of semidesert environments with shrub‐ and shortgrass‐steppes, indicating semiarid to arid conditions. Furthermore, the loess deposits do not show any evidence for cold‐adapted gastropod species. Therefore, we suggest that average July temperatures in the study area were above 10 °C, even during periods of loess deposition. Consequently, we propose that the limiting factor for tree growth during glacial periods was aridity, rather than temperature. In addition, we observe environmental differences between the various glacial times, with our results indicating a trend towards steadily increasing aridity in Southern Caucasia across the Middle to Late Pleistocene.